The Effect of Knowledge Management on Employee Performance (International Forum of Researchers and Lecturers, 2023)
This study aims to explain the effect of knowledge management on employee performance at Bank Madina Syariah Yogyakarta. The dependent variable in this study is employee performance. While the independent variable in this study is knowledge management on employee performance. The population in this study were all employees of Bank Madina Syariah Yogyakarta. The sampling method used was a saturated sample or all members of the research population. Data collection was carried out through distributing questionnaires and interviews. The analysis used is multiple linear regression technique. The results of the analysis show that knowledge management has a positive effect on employee performance.